Yam (Dioscorea spp. ) responses to the environmental variability in the Guinea in the Guinea Sudan zone of Benin - ZANNOU, A.; STRUIK, P. C.; RICHARDS, P.; ZOUNDJIHEKPON, JEANNE (My University, 2015)
This study analyzed the morphological characteristics and agronomic potentials of yam varieties (Dioscorea spp.) collected through the Guinea Sudan transition zone of Benin. Dioscorea cayenensis - D. rotundata were characterized as wingless; some varieties were spineless, others with few or dense, robust or thin, and short or prickled spines. There was variation in leaf shape, stem and leaf colour, tuber shapes and forking tendencies. The tuber flesh presented different colours, texture, oxidation colour, oxidation time, and ability to irritate. Dioscorea alata varieties were all spineless and winged stems, pentagonal or quadrangular. Various leaf and petiole colours, and tuber shape were observed. On average, the mean Shannon-Weaver index was 0.86 for the external morphology of the tuber, 0.55 for tuber flesh characteristics, and 1.13 for stem and leaf morphology. The pooled mean yield varied between 0.89 and 3.30 kg/heap for the early maturing varieties of the D. cayenensis - D. rotundata, 0.94 and 3.03 kg/heap for the late varieties, and ranged from 1.45 to 4.17 kg/heap for the D. alata varieties. The year effect was highly significant for variety-type group and species, and was larger than the genotypic effect. The genotypes by year interaction effects were highly significant.
Keywords: Dioscorea spp.; genotype by environment interaction; yield; yam varieties’ traits; Benin